2010
DOI: 10.1007/s12678-010-0003-4
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidation of Adsorbed CO on Pt(100) Electrodes in the Pre-peak Region

Abstract: The oxidation of CO adsorbed on Pt(100) electrodes in the pre-peak region (between 0.30 and 0.60 V) was studied using cyclic voltammetry, currenttime transients and Fourier transform infrared spectroscopy. According to our results, the pre-peak corresponds to the oxidation of a small fraction (<15%) of the CO adlayer, adsorbed on the terraces and adjacent to the step sites, the rate of CO oxidation being limited, within this potential region and at these high CO coverages, by the diffusion of CO to the reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 46 publications
(105 reference statements)
1
22
0
Order By: Relevance
“…The reaction mechanism is always affected by the fluxionality of metal clusters. In the CO oxidation reaction, the reconstruction of catalysts induced by reactant gases (CO on (Pt110) or oxygen on Pt(100) or Pd(110)) and the different adsorbates structures have a strong influence on CO oxidation reaction mechanism . In order to investigate the catalysts structure and CO oxidation reaction mechanism under realistic/industrial conditions, a lot of studies have been performed at the low and high reactant gases coverage .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction mechanism is always affected by the fluxionality of metal clusters. In the CO oxidation reaction, the reconstruction of catalysts induced by reactant gases (CO on (Pt110) or oxygen on Pt(100) or Pd(110)) and the different adsorbates structures have a strong influence on CO oxidation reaction mechanism . In order to investigate the catalysts structure and CO oxidation reaction mechanism under realistic/industrial conditions, a lot of studies have been performed at the low and high reactant gases coverage .…”
Section: Introductionmentioning
confidence: 99%
“…In the CO oxidation reaction, the reconstruction of catalysts induced by reactant gases (CO on (Pt110) or oxygen on Pt(100) or Pd(110)) and the different adsorbates structures have a strong influence on CO oxidation reaction mechanism. [19][20][21][22][23][24][25] In order to investigate the catalysts structure and CO oxidation reaction mechanism under realistic/industrial conditions, a lot of studies have been performed at the low and high reactant gases coverage. [19,[26][27][28][29][30] Under high O 2 pressure, for late-transition and noble metal elements such as Rh, Pd, Ag, and PtRh alloy, surface oxides have been proposed as the active phases.…”
Section: Introductionmentioning
confidence: 99%
“…Two oxidation regions are usually considered: the regions of 0.35-0.6 V (R.H.E.) before the oxidation peak [50][51][52][53] and from 0.6 V to higher potentials [54][55][56][57][58]. The authors [57] suggested, on the basis of differential electrochemical mass spectrometry data, that the changes of the Tafel slope at the variation of the scan speed are caused by the changes in the degree of the Pt surface coverage by OH particles and not by different CO oxidation mechanisms.…”
Section: Electrochemical Oxidation Of Rco2 Under Potentiodynamic Condmentioning
confidence: 99%
“…Now we are going to make some considerations about the diffusion of CO on surface during the electro-oxidation of the COads layer. Another way to interpret the influence of potential scan rate on the charge of CO pre-oxidation is to consider the limited surface diffusion of COads from any site on which this species is adsorbed to the reactive sites, as suggested for the electro-oxidation of COads on Pt(100) electrode (in principle with the COfree solution) [18]. For the Pt(111) surface in CO saturated solution at potentials in the preoxidation zone, by in situ high-speed scanning tunneling microscopy technique, diffusion of CO on surface (from any site to the reactive sites) is assigned to dynamics of defects in the COads compressed layer [22].…”
Section: Role Of Co In the Bulk Of The Solution On The Co Pre-oxidationmentioning
confidence: 99%
“…Due to its importance in terms of catalysis, many publications address the issue of CO pre-oxidation, in particular on Pt and Pt-based electrodes [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Generally, the divergences that exist on the topic concern the mechanism underlying the CO pre-oxidation phenomenon.…”
Section: Introductionmentioning
confidence: 99%